Design and synthesis of carbazole carboxamides as promising inhibitors of Bruton's tyrosine kinase (BTK) and Janus kinase 2 (JAK2). Issue 19 (1st October 2015) - Liu, Qingjie; Batt, Douglas G.; Lippy, Jonathan S.; Surti, Neha; Tebben, Andrew J.; Muckelbauer, Jodi K.; Chen, Lin; An, Yongmi; Chang, Chiehying; Pokross, Matt; Yang, Zheng; Wang, Haiqing; et al.
Graphical abstract: Abstract: Four series of disubstituted carbazole-1-carboxamides were designed and synthesised as inhibitors of Bruton's tyrosine kinase (BTK). 4, 7- and 4, 6-disubstituted carbazole-1-carboxamides were potent and selective inhibitors of BTK, while 3, 7- and 3, 6-disubstituted carbazole-1-carboxamides were potent and selective inhibitors of Janus kinase 2 (JAK2).